Adoption of smart and sustainable manufacturing practices: An exploratory study of Indian manufacturing companies. (April 2022) - Aggarwal, Ankur; Gupta, Sumit; Jamwal, Anbesh; Agrawal, Rajeev; Sharma, Monica; Dangayach, Govind S
Technological advancements and volatile customer demand over the globe have forced manufacturing industries to adopt smart and sustainable manufacturing practices. Now the industries are moving towards the Industry 4.0 to satisfy the mass customization demands as well as to create sustainable value creation. Indian industries are considered as one of major manufacturing hub for the automobile components in world and plays an important role in development of Indian economy. However, the adoption level of Smart manufacturing practices in India is limited due to technological, economical and other challenges. Industries are still struggling with the adoption of smart and sustainable manufacturing practices in the developing economies like India. Therefore, this study aims to find the relationship between sustainable and smart manufacturing practices in the emerging economies. In the present study we have used the hypothesis modelling approach to link the manufacturing competitiveness and top management commitment with the sustainable and smart manufacturing practices. The data is collected with the help of questionnaire survey from the Indian manufacturing industries. Further, Structural equation modelling approach (SEM) is used. The results of this study highlights how manufacturing industries can adopt the smart and sustainable manufacturing practices in the developing economies like India.